Development of emulsion fuel mixer system - Muhammad Nor Ridzuan, M. Taifor (2013)
It is an uncommon belief that an emulsified biodiesel may assist in lowering diesel engine emissions such as Nitrogen Oxide, NOx and other harmful forms of particulate matter whilst maintaining its performance. Emulsion is essentially a dispersion phenomenon in which the dispersed phase is composed of small globules of a liquid. This study entails the development of an emulsifier for emulsified biodiesel which incorporates the design and fabrication of the mixer system. By utilizing the static mixer, this study describes the obtaining process of water in oil emulsifications which assisted by tween 80 and span 80 surfactants. This is ensued by data collection and analysis from the emulsified biodiesel product obtained from the aforementioned fabricated mixer system. The quality of the product was evaluated by the stability of the dispersion phase. By this research, the system were able to produce the emulsified biodiesel but it didn’t comply the desired result as the product dispersed only a few minutes due to injector problems